ANALISIS BALIK KUAT GESER TANAH TERSTABILISASI SEMEN DENGAN METODE NUMERIK - Muhammad Toyeb (Racic : Rab Construction Research, 2020)
Shear strenght is a parameter to soils strenght analysis. Shear strenght can be obtained from laboratorium test that interpreted as stress and strain. Soil tests had done on soil stabilization of cement with mixing 5%; 10%; 15% of content. Soil tests were used by triaxial test of unconsolidated undrained (triaxial UU) with cell pressure at 50; 100; 200 kN/m2 and unconfined compression test. The test specimens were disturbed soil samples which compacted and remolded, and then carry out curing for 0; 3; 7; 14; 28 days. The laboratory test results were back analysis in Plaxis 2D by using Mohr-Coulumb and Hardening Soil model later. The Mohr-Coulumb and Hardening Soil model had deviator stress results was almost equal to the test results of triaxial UU and unconfined compression test. Especially of strain by Mohr-Coulumb model, shew the lower strain than be showed by triaxial UU test and unconfined compression test. The Hardening Soil model, provides fluctuating strain results of triaxial UU test because it is affected by the application of cell pressure (Ïƒ3) and it provides greater strain results from unconfined compression test. Keywords: Triaxial UU, Unconfined Compresssion, Stress and Strain, Plaxis 2D